Status of rheumatoid arthritis practice and treatment in Sudan - Zainab Abdelgadir Hassan Ali; Ghada Omer Hamad Abd El-Raheem; Mounkaila Noma (Scientific African, 2023)
Rheumatoid Arthritis is a chronic immune mediated predominantly articular inflammatory disease that may lead to joint destruction and disability. This study described the status of Rhematoid Arthritis among Sudanese patients. A multi-center descriptive cross-sectional study was implemented. 90 patients were involved. Morisky scale was used to assess the adherence to rheumatoid medications. Data were analysed using SPSS-23. Chi-square and regression were used to establish the relationship between adherence and the associated factors. Tests were considered significant when p < 0.05.Females comprised 93.3 %. A statistically significant association (p = 0.01) was found between the disease duration and female gender. Hydroxychloroquine was the mostly used medication (83.3 %). 69.7 % of the patients had low adherence to rheumatoid medications and none of the patients had high adherence. A statistically significant association (p = 0.025) was found between adherence and medication unavailability. The number of pills and side effects of anti-rheumatic medications were the statistically significant predictors of adherence with a p-value of respectively 0.030 and 0.009.In Sudan, the status of Rhematoid arthritis was understudied, for this reason our study was developed to give a picture about the status of this disease among Sudanese population. We studied the characteristics of the patients, the distribution of the disease and the factors related to poor adherence. Patients in all the states of Sudan are suffering because of the lack of medical access as all rheumatology centers were located only in Khartoum state. Nevertheless, majority of patients had lack of knowledge about their disease condition, and suffered from the high products prices as well as market unavailability. This study highlighted the burden of this disease on Sudanese society and the urgent need for the concerned authorities to develop support programs and policies to improve the healthcare status of Sudanese population with rheumatoid arthritis.